Gut Microbiome and Disorders of the Gastrointestinal Tract - Alexander Hammerhøj; John Mark Gubatan; Ole Haagen Nielsen (Microorganisms, 2024)
The protective intestinal epithelial barrier is constantly exposed to more than 100 trillion commensal microorganisms (bacteria, archaea, viruses, and fungi), i [...]